2013
DOI: 10.1111/jpy.12096
|View full text |Cite
|
Sign up to set email alerts
|

Gene silencing inFucusembryos: developmental consequences ofRNAi‐mediated cytoskeletal disruption

Abstract: Brown algae (Phaeophyceae) are an important algal class that play a range of key ecological roles. They are often important components of rocky shore communities. A number of members of the Fucales and Ectocarpales have provided models for the study of multicellular evolution, reproductive biology and polarized development. Indeed the fucoid algae exhibit the unusual feature of inducible embryo polarization, allowing many classical studies of polarity induction. The potential of further studies of brown algae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…A protocol for genetic transformation does not exist for Ectocarpus (or for any other brown alga) but injection of double stranded RNA into zygotes of the brown alga Fucus has been shown to induce an RNA interference (RNAi) response, leading to knockdown of target gene expression (Farnham et al, 2013). We recently adapted this Fucus RNAi protocol for Ectocarpus, using synthetic siRNA molecules instead of long double-stranded RNA molecules and a lipofectant specifically adapted for dsRNA delivery to introduce the siRNAs into the cell rather than the microinjection procedure used for Fucus (Macaisne et al, 2017).…”
Section: Genetic Analysis and Identification Of The Dis Genementioning
confidence: 99%
“…A protocol for genetic transformation does not exist for Ectocarpus (or for any other brown alga) but injection of double stranded RNA into zygotes of the brown alga Fucus has been shown to induce an RNA interference (RNAi) response, leading to knockdown of target gene expression (Farnham et al, 2013). We recently adapted this Fucus RNAi protocol for Ectocarpus, using synthetic siRNA molecules instead of long double-stranded RNA molecules and a lipofectant specifically adapted for dsRNA delivery to introduce the siRNAs into the cell rather than the microinjection procedure used for Fucus (Macaisne et al, 2017).…”
Section: Genetic Analysis and Identification Of The Dis Genementioning
confidence: 99%
“…Most of the research has focused on members of the Fucales. Despite promising technologies for molecular gene function analysis and forward genetics being developed recently (Farnham et al 2013), the use of fucoid algae in developmental biology has dwindled over the years, largely because of the poor amenability to genetic and molecular studies (Yang 2008). Because it is easily cultured (Vielhaben 1963;Müller 1962;Kumke 1973), Dictyota has been proposed as a possible model complementary to fucoids (Bogaert et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has demonstrated that injection of double-stranded RNA into zygotes of the brown alga Fucus induces an RNA interference (RNAi) response, leading to knockdown of target gene expression (Farnham et al, 2013). RNAi therefore represents a potential approach to investigate gene function in brown algae, but a modification to the Fucus protocol was required because microinjection is not feasible for Ectocarpus due to the small size of its cells.…”
Section: Disruption Of Imm Function By Rna Interferencementioning
confidence: 99%